2015
DOI: 10.6090/jarq.49.85
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PSPA Cell Differentiation,an Established Pig Preadipocyte Cell Line as an In Vitro Model for Pig Fat Development

Abstract: We have established a clonal porcine subcutaneous preadipocyte cell line for the first time. This cell line, named PSPA, shows a fibroblast-like phenotype and keeps on growing under growth medium even after reaching confluence. Adipose conversion occurs only when confluent cultures are stimulated with insulin, dexamethasone, biotin, pantothenate, and octanoate. Following exposure to this differentiation medium, growth was arrested immediately without mitotic expansion and PSPA cells exhibited a marked increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…OP9 is also murine derived and useful as a stromal line capable of rapid, high-efficiency lipid accumulation (Wolins et al, 2006). There is precedent for the establishment of adipogenic cell lines from agriculturally-relevant species, as evidenced by the porcine PSPA line and the bovine BIP lines reported in the literature, but none are commercially available (Aso et al, 1995;Nakajima, 2015). The development and commercialization of similar lines from common meat-producing species would provide an attractive source for fat production for food applications.…”
Section: Immortalized Adipogenic Cell Linesmentioning
confidence: 99%
“…OP9 is also murine derived and useful as a stromal line capable of rapid, high-efficiency lipid accumulation (Wolins et al, 2006). There is precedent for the establishment of adipogenic cell lines from agriculturally-relevant species, as evidenced by the porcine PSPA line and the bovine BIP lines reported in the literature, but none are commercially available (Aso et al, 1995;Nakajima, 2015). The development and commercialization of similar lines from common meat-producing species would provide an attractive source for fat production for food applications.…”
Section: Immortalized Adipogenic Cell Linesmentioning
confidence: 99%
“…8,9 . Several porcine cell lines with adipogenic potential have also been reported that can maintain proliferation over 30 passages [10][11][12][13] . However, all cell lines have relatively low adipogenic e ciency, and none of them have been proven or available for using in cell-cultured fat.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 . Several porcine cell lines with adipogenic potential have also been reported that can maintain proliferation over 30 passages [10][11][12][13] . However, all cell lines have relatively low adipogenic efficiency, and none of them have been proven or available for using in cell-cultured fat.…”
mentioning
confidence: 99%